A tennis-based health program for middle-aged men who are at risk for heart disease. Issue 2 (30th March 2017) - Jr, Flavio Rosa; Fuentes, Juan Pedro; Remor, Aline Pertile; Ghisoni, Karina; Silveira, Paulo Cesar Lock; Costa, Vitor; Prim, Rafael Luiz; Scheffer, Débora da Luz; Jr, Aderbal Silva Aguiar; Guglielmo, Luiz Guilherme Antonacci; Latini, Alexandra
No abstract available